Validitas dan Reliabilitas Butir Soal Berbasis Kemampuan Berpikir Kritis Pada Materi Listrik Dinamis - Ika Ningtiyas, Retno; Sahal, Muhammad; Gusmeri, Yeni (Kilau Publishing, 2023)
The purpose of this research is to develop questions based on critical thinking on dynamic electricity material and to determine the feasibility of the questions developed in terms of validity and reliability aspects. This type of research is development work according to the R&K (Research and Development) model. The research sample consisted of 24 students. From the test results it is known that the questions developed are declared valid and reliable. The aspect of validity consists of internal validity and external validity, where internal validity is carried out by a validator whose level of validity is in the good category and is suitable for use subject to previous controls. At the same time, external validity was carried out by testing a number of students. The result is 16 out of 24 questions declared valid. Next is the reliability factor with a score of 0.81. This value is greater than 0.8 so that it is declared reliable and is in the very high category.